Thin Graphene–Nanotube Films for Electronic and Photovoltaic Devices: DFTB Modeling - Dmitry A. Kolosov; Vadim V. Mitrofanov; Michael M. Slepchenkov; Olga E. Glukhova (Membranes, 2020)
Supercell atomic models of composite films on the basis of graphene and single-wall carbon nanotubes (SWCNTs) with an irregular arrangement of SWCNTs were built. It is revealed that composite films of this type have a semiconducting type of conductivity and are characterized by the presence of an energy gap of 0.43–0.73 eV. It was found that the absorption spectrum of composite films contained specific peaks in a wide range of visible and infrared (IR) wavelengths. On the basis of calculated composite films volt-ampere characteristics (VAC), the dependence of the current flowing through the films on the distance between the nanotubes was identified. For the investigated composites, spectral dependences of the photocurrent were calculated. It was shown that depending on the distance between nanotubes, the maximum photocurrent might shift from the IR to the optical range.